A conceptual framework for improving effectiveness of risk management in supply networks. Issue 1 (8th February 2020) - Chaudhuri, Atanu; Ghadge, Abhijeet; Gaudenzi, Barbara; Dani, Samir
Abstract : Purpose: The purpose of the paper is to develop a conceptual framework for improving the effectiveness of risk management in supply networks following a critical literature review. Design/methodology/approach: A critical review of 91 scholarly journal articles published between 2000 and 2018 supports the development of an integrated conceptual framework. Findings: The findings emphasize that supply chain integration (SCI) can have both a positive and negative impact on the effectiveness of risk management in supply networks. It is possible to have a positive effect when SCI can be used to develop competencies in joint risk planning within the organization and with wider supply network members and, in turn, to develop collaborative risk management capabilities. Supply network characteristics can influence whether and the extent to which SCI has a positive or negative impact on risk management effectiveness. Research implications: The conceptual framework can be used to empirically assess the role of SCI for effective risk management. Dynamic evaluation of the effectiveness of risk management and potential redesign of the supply network by considering other contingent factors are some future research avenues. Practical implications: There is a need for developing specific competencies in risk planning within organizations and joint risk planning with supply network members which, in turn, can help develop collaborative risk management capabilities to improve the effectiveness of risk management in supply networks. Network characteristics will influence whether and the extent to which SCI results in the effectiveness of risk management. Originality value: Moving beyond recent (systematic) reviews on supply chain risk management, this study develops a novel conceptual framework interlinking SCI and the effectiveness of risk management while considering network characteristics.